KEJAHATAN TRANSNASIONAL NARKOBA DI PERBATASAN INDONESIA-MALAYSIA (STUDI KASUS: KEPULAUAN MERANTI TAHUN 2015-2019) - Destika Nespuwani; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The purpose of this research is to find out how transnational crime is on the border of the Meranti Islands-Malaysia and the countermeasures carried out by the local government and officials.               This type of research used by the author used by qualitative research methods, namely descriptive data procedures. Data collection techniques were carried out by using library research methods and interviews with several sources. This study uses books, journals, media, and interviews as a source of support for the research completion process. The perspective used is a constructivist perspective with a group analysis level.               This study explains that the transnational drug crime that occurred on the border of the Meranti Islands-Malaysia. Strategic geographical conditions located on the border and the Malacca Strait, tended security, and poverty rates that make the Meranti Islands one of the gateways for drug smuggling from Malaysia. Smuggling is carried out through direct sea routes and transit routes with the modus operandi of Opera Skip, smuggling and transactions in the early hours of the morning as well as deceiving officers by throwing drug goods into the sea. Weak legal and security measures give the impression of a low effect so that this transnational crime continues.Keywords: Transnational Crime, Drugs, Meranti Islands, Malaysia